Translation Shifts Found in The Crown Netflix Series - Mahendhi, Ni Luh Made Risma; Pratama, Agus Darma Yoga; Susanthi, I Gusti Agung Ayu Dian (Interference: Journal of Language, Literature, and Linguistics, 2024)
Abstract. This study, titled Translation Shifts in The Crown Netflix Series, aims to identify various types of translation shifts and assess the functional equivalence of these shifts within the context of the Netflix series The Crown. The research adopts a qualitative approach, utilizing ten episodes from one season as the primary data. Data collection focused on examining the translated texts accompanying each episode. The analysis is grounded in Catford's theory of translation shifts, which categorizes shifts into two main types: level and category shifts, further subdivided into structure, unit, class, and intra-system shifts. Additionally, the study applies Nida and Taber's functional equivalence theory, distinguishing between formal and dynamic equivalence. The findings reveal 100 level shifts and a significant occurrence of category shifts, with 120 structure shifts, 40 class shifts, 100 unit shifts, and 60 intra-system shifts. Formal equivalence emerged as the most frequently identified type among the translation shifts. The results provide critical global implications for translation practices in media, particularly highlighting the balance between preserving original meanings and adapting content for target audiences across different cultural and linguistic contexts. This research underscores the need for nuanced translation strategies in globally distributed media content. Keywords: Functional equivalence, Qualitative analysis, Translation shifts